Proceedings of the 2020 Conference on Empirical Methods in Natural Language Processing (EMNLP) 2020
DOI: 10.18653/v1/2020.emnlp-main.15
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Probing through Dimension Selection

Abstract: Most modern NLP systems make use of pretrained contextual representations that attain astonishingly high performance on a variety of tasks. Such high performance should not be possible unless some form of linguistic structure inheres in these representations, and a wealth of research has sprung up on probing for it. In this paper, we draw a distinction between intrinsic probing, which examines how linguistic information is structured within a representation, and the extrinsic probing popular in prior work, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…Since the Gaussian distribution is the maximum entropy distribution given a mean and covariance matrix, it makes the fewest assumptions and is therefore a reasonable default. Hennigen et al (2020) found that embeddings sometimes do not follow a Gaussian distribution, but it is unclear what alternative distribution would be a better fit, so we will assume a Gaussian distribution in this work.…”
Section: Connection To Mahalanobis Distancementioning
confidence: 99%
“…Since the Gaussian distribution is the maximum entropy distribution given a mean and covariance matrix, it makes the fewest assumptions and is therefore a reasonable default. Hennigen et al (2020) found that embeddings sometimes do not follow a Gaussian distribution, but it is unclear what alternative distribution would be a better fit, so we will assume a Gaussian distribution in this work.…”
Section: Connection To Mahalanobis Distancementioning
confidence: 99%
“…Alain and Bengio, 2016;Hewitt and Manning, 2019;Hall Maudslay et al, 2020) or a subset of neurons at a time (e.g. Torroba Hennigen et al, 2020;Mu and Andreas, 2020;Durrani et al, 2020). However, restricting our analysis this way seems arbitrary.…”
Section: Ease Of Extraction and Previous Workmentioning
confidence: 99%
“…The first part of the tutorial covers methods that align neurons to human interpretable concepts or study the most salient neurons in the network. We cluster these methods into four groups i) Visualization Methods (Karpathy et al, 2015;Li et al, 2016a), ii) Corpus Selection (Kádár et al, 2017;Poerner et al, 2018;Na et al, 2019;Mu and Andreas, 2020b), iii) Neuron Probing (Dalvi et al, 2019a;Lakretz et al, 2019;Valipour et al, 2019;Durrani et al, 2020) and iv) Unsupervised Methods (Bau et al, 2019;Torroba Hennigen et al, 2020;Michael et al, 2020). We will discuss evaluation methods that are used to measure the effectiveness of an interpretation method, such as accuracy, control tasks (Hewitt and Liang, 2019) and ablation studies (Li et al, 2016b;Lillian et al, 2018;Dalvi et al, 2019a;Lakretz et al, 2019).…”
Section: Descriptionmentioning
confidence: 99%